Intergenerational Transmission of Education and Mediating Channels: Evidence from Compulsory Schooling Reforms in Germany - Marc Piopiunik (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
This paper estimates the causal effect of an additional year of parents schooling on theirchildrens education, exploiting compulsory schooling reforms that were implemented inall West German states between 1946 and 1969. Although previous research indicatesthat these reforms had no effects on earnings or political behaviour, I find that an additionalyear of schooling women strongly affects their sons education. Based on severaldatasets, numerous channels that might mediate the positive impact of mothers educationare investigated. Most importantly, individuals with more schooling value childrenseducational success as more important.
Keywords: I20; J62; 330; Intergenerational mobility; education; compulsory schooling reforms; SOEP; Schulrecht; Schulbesuch; Mütter; Bildungsniveau; Generationenbeziehungen; Kinder; Schätzung; Deutschland